Job Crafting As A Mediating Variable Between Proactive Personality And Employee Performance: A Review On Village Owned Enterprises - Retno Kurniasih; Wahyudin Wahyudin; Najmudin Najmudin; Sudarto Sudarto (Citakonsultindo, 2024)
This study aims to examine the impact of proactive personality on employee performance and assess the role of job crafting as a mediating factor in the connection between proactive personality and employee performance. The research will utilize a quantitative methodology and encompass the entire population of 53 employees from BUMDes in Sokaraja District as the research sample. The sampling approach use saturated samples when the whole population is utilized as a research sample. The data was analyzed using SmartPLS. The data analysis revealed the following findings: 1) Proactive personality has a positive effect on employee performance, 2) Job crafting influences employee performance, 3) Proactive personality has a positive effect on job crafting, and 4) Job crafting as a mediator between proactive personality and employee performance. Implications that can be inferred from the conclusions above are that BUMDes parties are anticipated to adopt a more inclusive approach, rather than only employing a hierarchical structure in BUMDes management, to provide employees with greater autonomy to engage in job crafting.